2015
DOI: 10.3133/sir20145158
|View full text |Cite
|
Sign up to set email alerts
|

Baseline water-quality sampling to infer nutrient and contaminant sources at Kaloko-Honokōhau National Historical Park, Island of Hawai‘i, 2009

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…The lack of removal of REEs from solution in the Kona Coast mixing experiments, and by inference, the Kona Coast subterranean estuary, instead likely reflects the much lower dissolved organic carbon concentrations, as well as the lower dissolved Fe and Mn concentrations, of these groundwaters compared to previously studied rivers and associated surface estuaries that exhibit REE removal (Table 3). For example, DOC concentrations are between 4 and 21 times greater in these rivers and their associated estuaries than in Kona Coast groundwaters, excluding groundwater from the Honokohau Harbor well, which again receives effluent from the WWTF (e.g., Parsons et al, 2008;Hunt, 2014;Prouty et al, 2016; Table 3). Dissolved Fe concentrations in these rivers and surface estuaries are also commonly between 2-and 5-fold higher than in Kona Coast groundwaters (Tables 2, 3).…”
Section: Mixing Experimentsmentioning
confidence: 99%
“…The lack of removal of REEs from solution in the Kona Coast mixing experiments, and by inference, the Kona Coast subterranean estuary, instead likely reflects the much lower dissolved organic carbon concentrations, as well as the lower dissolved Fe and Mn concentrations, of these groundwaters compared to previously studied rivers and associated surface estuaries that exhibit REE removal (Table 3). For example, DOC concentrations are between 4 and 21 times greater in these rivers and their associated estuaries than in Kona Coast groundwaters, excluding groundwater from the Honokohau Harbor well, which again receives effluent from the WWTF (e.g., Parsons et al, 2008;Hunt, 2014;Prouty et al, 2016; Table 3). Dissolved Fe concentrations in these rivers and surface estuaries are also commonly between 2-and 5-fold higher than in Kona Coast groundwaters (Tables 2, 3).…”
Section: Mixing Experimentsmentioning
confidence: 99%
“…3). A recent study reported that B isotopes did not work well as a tracer for sewage in brackish waters (Hunt, 2014).…”
Section: Tide Pool Watermentioning
confidence: 99%
“…δ 15 N and δ 18 O in NO 3 and δ 11 B along upland-lowland gradients have been used to determine N sources to groundwater in several studies (Leenhouts et al, 1998;Seiler, 2005;Hunt, 2006, Hunt, 2014Xue et al, 2014). However, to our knowledge, our study is the first to apply this multi-isotope approach to detect N sources to coastal waters along an onshore-offshore gradient.…”
Section: Tide Pool Watermentioning
confidence: 99%
See 1 more Smart Citation
“…These data have enabled the NPS to identify potential sources of anthropogenic nutrient input including a transient spike of nitrogen‐enriched irrigation water attributable to a neighboring golf course (Fig. ; Hunt , Raikow and Farahi ), and pronounced changes in nutrient levels at some locations proximal to urban development (Fig. ; Raikow and Farahi ).…”
Section: Resultsmentioning
confidence: 99%